Geothermal Energy in Nigeria: Assessing Its Potential and Environmental Impacts for Sustainable Development - Samuel Bassey (International Journal of Energy and Thermal Applications, 2024)
This study explores the possibility of using geothermal energy to address Nigeria's electricity generation issues sustainably. Significant potential for high-output power generation from geothermal resources is revealed by analyzing the geological features of the nation. Environmental issues including pollutant emissions and ecosystem damage are explored with the benefits of geothermal energy, such as its small land footprint and dependability. The purpose of the article is to identify possible geothermal energy sources in Nigeria, investigate their uses, and discuss the environmental risks related to geothermal power facilities. This research helps Nigeria and other countries develop a sustainable energy future by providing in-depth analysis and creative solutions.
Keywords: Electricity Generation; Environmental impact; Nigeria; Power plant efficiency; and sustainable development; geothermal energy; pollution emissions; renewable resources; sustainable energy